Voices from the dead: the uneasy case of indigenous cultural expression - Abdul Ghani Azmi, Ida Madieha (Emerald Insight, 2017)
Purpose Traditional cultural expression (TCE) includes music, dance, art, designs, names, signs and symbols, performances, ceremonies, architectural forms, handicrafts and narratives or many other artistic or cultural expressions [World Intellectual Property Office (WIPO)]. To constitute TCEs, the expressions must form part of the identity and heritage of a traditional or indigenous community and need to be passed down from generation to generation (Kuprecht, 2014). This paper aims to analyse the protection of TCE in Malaysia by focusing on the Mah Meri tribe. This paper examines copyright over TCE, recordation as a means of preserving a dying tradition and customary practices and native law.